OBSERVATIONS ON THE BIOLOGY AND FISHERY OF METAPENAEUS BREVICORNIS (M. EDW.> IN THE HOOGHLY ESTUARINE SYSTEM - Rajyalakshmi, T (Indian Journal of Fisheries, 2011)
SEVERAL species of Penaeid prawns ascend the Hooghly estuarine system,as juveniles, where they contribute considerably to the commercial catches.Such of those juveniles that enter ' bheris' and paddy fields constitute thevarieties that are cultured "widely in deltaic Bengal. Amongst these variousspecies Metapenaeus brevicornis (M. Edw.) locally known as ' Dhanbonechingri' is the " commonest Penaeid of Bengal occurring very plentifullyin the delta of Ganges" (Chopra, 1939 and 1943; Panikkar and Menon,1955). Alcock (1906) has recorded the distribution of the species as in India,Mauritius and Borneo. He has also recorded that the species rarely attainsa length of 5". In the present studies also the largest female recorded is120 mm. (4-75"). Considering the commercial importance of this speciesa knowledge of various aspects of its biology has been considered essentialboth for a proper management of its fishery in the estuaries as well as forrecommendation of its large-scale culture, and hence this study.